2017
DOI: 10.1007/s00280-017-3434-2
|View full text |Cite|
|
Sign up to set email alerts
|

Innovative intraoral cooling device better tolerated and equally effective as ice cooling

Abstract: PurposeMost of the patients who receive myeloablative therapy prior to stem cell transplantation develop oral mucositis (OM). This adverse reaction manifests as oral mucosal erythema and ulcerations and may require high doses of morphine for pain alleviation. OM may also interfere with food intake and result in weight loss, a need for parenteral nutrition, and impaired quality of life. To date, there have been very few studies of evidence-based interventions for the prevention of OM. Cryotherapy, using ice chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 18 publications
8
27
1
Order By: Relevance
“…We also demonstrated that cold air is capable of reducing the temperature in the oral mucosa by 10.9 °C after just 5 min of treatment with an average temperature of 4.0 °C. These results are comparable to those of Walladbegi et al [20] and Svanberg et al [19] who demonstrated that the cooling of the oral mucosa with ice after 60 min of treatment in healthy volunteers led to a temperature reduction of 8.1 °C and 12.9 °C, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We also demonstrated that cold air is capable of reducing the temperature in the oral mucosa by 10.9 °C after just 5 min of treatment with an average temperature of 4.0 °C. These results are comparable to those of Walladbegi et al [20] and Svanberg et al [19] who demonstrated that the cooling of the oral mucosa with ice after 60 min of treatment in healthy volunteers led to a temperature reduction of 8.1 °C and 12.9 °C, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…In randomized clinical trials, cooling has been achieved using ice and ice-chips for 30-60 min during chemotherapy infusions [15,17,18]. Studies have shown that OC with ice for 60 min reduces the temperature in the oral mucosa by 8.1-12.9 °C [19,20]. However, the intervention is experienced as troublesome for many of the patients.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent OM, an intraoral cooling device (Cooral) has been developed. 7 Cooral consists of closed conduits with continuously circulating water, to cool the cheeks, lips, floor of the mouth, tongue gums and hard palate. By offering Cooral, we intend to prevent OM.…”
Section: Introductionmentioning
confidence: 99%
“…Pre‐incubation temperatures for the TEOM models were selected based on 2 separate studies on healthy volunteers where an approximate mean temperature of 25‐30°C was obtained in the oral mucosa . These temperatures were further selected with an interval of 5°C as they represented clinically relevant temperatures.…”
Section: Discussionmentioning
confidence: 99%